Biochemical and Growth Responses of Moringa peregrina (Forssk.) Fiori to Different Sources and Levels of Salinity - M Salehi; N Majnun Hoseini; H Naghdi Badi; D Mazaheri (Institue of Medicinal Plants, ACECR, 2012)
Background: As Moringa peregrina is a valuable medicinal plant in traditional medicine, it is necessary to determine responses of this plant to salinity.   Objective: To determine some biochemical and growth responses of Moringa peregrina to salinity at the seedling stage.   Methods: This experiment was conducted in Institute of Medicinal Plants-ACECR, on base of factorial experiment as completely randomized design with four replications. The treatments included a combination of 3 different sources of salt (NaCl, NaCl + CaCl2 and natural saline water) and eight levels of salinity (control, 2, 4, 6, 8, 10, 12 and 14 dS/m).   Results: The results showed that the salinity levels had significant effect (p < 0.01) on the studied traits. Although the sources of salinity hadn't a significant effect on shoot and root length, other traits were significantly (p < 0.01) affected by it. This study indicated that Moringa peregrina hadn't reduction in growth parameters and seedling emergence up to 6 dS/m, then these traits significantly decreased with increasing salinity. Proline and carbohydrate content as compatible organic solutes increased with increasing salinity and these results indicated an important role of proline and carbohydrates in Moringa peregrina tolerance to salinity.  Conclusion: The survival and no reduction in seedling emergence and growth parameters up to 6 dS/m indicated that moringa was a salt tolerant species at the early growth stage.